2006
DOI: 10.1007/s10620-006-3093-3
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Gene Mutations Are Rare in Nondysplastic Barrett's Esophagus

Abstract: In search of potential prognostic markers, we analyzed a large series of tissues of Barrett's esophagus and samples of adenocarcinomas arising in the terrain of Barrett's esophagus for TP53 gene mutations by direct sequencing of exons 5 to 9 of the TP53 gene. While 9 of 21 adenocarcinomas tested (42.9%) contained a TP53 mutation, none of 24 samples from Barrett's esophagus were mutated. This observation suggests that TP53 gene mutation may be a relatively late event in the progression from nondysplastic Barret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Like the primary patient tissues, all were Cytokeratin, EpCam and p53 positive, confirming respectively the epithelial nature of the cells; their derivation from transformed metaplastic columnar-type epithelium (rather than adjacent normal squamous oesophageal epithelium); and neoplastic phenotype, as oesophageal p53 staining is not found in non-dysplastic Barrett's Oesophagus. [11, 12] Trefoil Factor 3 (TFF3) is involved in protection, maintenance and repair of the intestinal mucosa, [13] specific for cells with an intestinal phenotype, [14] and is a reliable marker of metaplastic change in the oesophagus. [15] It was present in all of the primary patient cancer tissue, but absent in the feeder layer culture of the close-to-patient cancer cells, however expression was restored in both the 3D-TGA with mesenchymal support (Figure 1E, 1F) and xenografts (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Like the primary patient tissues, all were Cytokeratin, EpCam and p53 positive, confirming respectively the epithelial nature of the cells; their derivation from transformed metaplastic columnar-type epithelium (rather than adjacent normal squamous oesophageal epithelium); and neoplastic phenotype, as oesophageal p53 staining is not found in non-dysplastic Barrett's Oesophagus. [11, 12] Trefoil Factor 3 (TFF3) is involved in protection, maintenance and repair of the intestinal mucosa, [13] specific for cells with an intestinal phenotype, [14] and is a reliable marker of metaplastic change in the oesophagus. [15] It was present in all of the primary patient cancer tissue, but absent in the feeder layer culture of the close-to-patient cancer cells, however expression was restored in both the 3D-TGA with mesenchymal support (Figure 1E, 1F) and xenografts (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the p53 mutation was an important step in the progression toward adenocarcinoma. Although p53 mutations are common in adenocarcinoma, they are relatively uncommon in nondysplastic Barrett's esophagus (52).…”
Section: Studies Of P53 and Barrett's Esophagusmentioning
confidence: 99%
“…Recently, Novotna et al, by direct sequencing of exons 5 to 9 of the p53 gene, reported lack of p53 mutations in 24 BE cases in the absence of dysplasia. 24 These data suggest that p53 mutation is rare, if present at all, before the development of dysplasia in BE. Downregulation of APC expression was observed in HGD stage, and was markedly decreased in EC.…”
Section: Discussionmentioning
confidence: 79%